1995
DOI: 10.1073/pnas.92.12.5530
|View full text |Cite
|
Sign up to set email alerts
|

Neural-network-based classification of cognitively normal, demented, Alzheimer disease and vascular dementia from single photon emission with computed tomography image data from brain.

Abstract: Single photon emission with computed tomography (SPECT) hexamethylphenylethyleneamineoxime technetium-99 images were analyzed by an optimal interpolative neural network (OINN) algorithm to determine whether the network could discriminate among clinically diagnosed groups of elderly normal, Alzheimer disease (AD), and vascular dementia (VD) subjects. After initial image preprocessing and registration, image features were obtained that were representative of the mean regional tissue uptake. These features were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 16 publications
(13 reference statements)
0
24
1
Order By: Relevance
“…The current study aimed to classify and identify the three groups of patients with Alzheimer disease, patients with mental decline and the healthy elderly people. The obtained results showed that the artificial neural network method had effects on the diagnosis of brain images and other areas (14).…”
Section: Review Of the Literaturementioning
confidence: 82%
“…The current study aimed to classify and identify the three groups of patients with Alzheimer disease, patients with mental decline and the healthy elderly people. The obtained results showed that the artificial neural network method had effects on the diagnosis of brain images and other areas (14).…”
Section: Review Of the Literaturementioning
confidence: 82%
“…Individual studies evaluating the diagnostic utility of SPECT imaging, however, have differed in terms of sample size, patient characteristics, clinical diagnostic criteria employed, cognitive testing, and imaging acquisition [17,29]. Studies to date have also focused on the diagnostic utility of SPECT in older adults with AD compared, predominantly, to cognitively unimpaired controls [30]. In those with EOD, symptoms often present differently than in older adults, with symptoms including aphasia, apraxia, agnosia, and visual disturbance rather than typical amnestic syndromes [31].…”
Section: Discussionmentioning
confidence: 99%
“…Mean uptake values are averaged within these regions and compared within or between subjects [12]. Quantitative methods, such as the automated multi-ROI programme 3DSRT [13,14], statistical parametric mapping [15][16][17], discriminant function analysis [18][19][20], three-dimensional stereotactic surface projection [21] and neural network analysis [22][23][24][25][26] have been added to the research tools available in PET and SPECT. Adding structural information from MRI or CT improves clinical and research interpretations of functional scans [19,[27][28][29][30].…”
Section: Image Analysis Methodsmentioning
confidence: 99%